Long-term variation of black carbon and PM2.5 in Beijing, China with respect to meteorological conditions and governmental measures. (May 2016) - Chen, Yuan; Schleicher, Nina; Fricker, Mathieu; Cen, Kuang; Liu, Xiu-li; Kaminski, Uwe; Yu, Yang; Wu, Xue-fang; Norra, Stefan
Abstract: Black carbon (BC) and PM2.5 were studied for nine years from 2005 to 2013 in the Beijing urban area. The overall weekly average mass concentrations of BC and PM2.5 were 4.3 and 66.8 μg/m³. PM2.5 annual means of the nine years are around 2 times of the standard (GB3095-2012) in China, and are 5–7 times higher than the WHO standard. The Beijing Olympic Games in 2008 was a milestone to mitigate aerosol pollution. Temporal distribution of BC shows a distinct declining trend, and annual mean mass concentrations of PM2.5 after 2008 were lower than those before 2008 but increased from 2011 to 2013. Wind rose plots show that high BC concentrations are usually associated with low wind speed of northeastern or southwestern winds, generally causing poor visibility. Governmental mitigation measures such as traffic restriction despite increased motor vehicle numbers and gasoline consumption and industry relocation with declining consumption of coal and coke were successful in reducing BC emissions. Annual mean of BC was reduced by 38% in 2013 compared to 2005. However, BC contamination in Beijing is still severe when compared to other urban areas around the world. Highlights: PM2.5 and black carbon in Beijing were studied for nine years. The influence of meteorological factors on PM2.5 and BC were investigated. The governmental measures on mitigating atmospheric particulate emissions were successful. August 2008 (the Olympic Games period) showed the lowest monthly BC concentration. BC contamination in Beijing is still severe when compared to other urban areas. Abstract : This study presents the long-term PM2.5 and BC variation, the correlations with meteorological conditions and the effectiveness of mitigation measures in reducing the emissions.